ANALYSIS AND INTERPRETATION OF FERDINAND NGWABA’S “THIS SECOND DEATH” AND CLAUDE MCKAY’S “IF WE MUST DIE” - Marie-Antoinette VUVU DIKUMBANZILA (Ziglôbitha, 2023)
ABSTRACT : This article focuses on the analysis and interpretation of the two poems: “This Second Death” by Ngwaba and “If We Must Die” by McKay. It aims at proving the parallelism between the two texts to support the idea stating that literature constitutes the very tool through which people are called to learn about human issues taking place within the universe. In fact, any deed occurring in the universe is expressed through the use of communicative events known as discourse. Ngwaba (2009:18) points out that literature is an interactive discourse used for communication. However, to decipher the meaning hidden in the text requires resorting to the use of some specific techniques, such as the analysis and interpretation of written and oral texts. Those techniques work in correlation with science as hermeneutics. Within these techniques can be drawn some sub branches, such as paraphrasing, use of context, dramatization, etc. to penetrate the inner mind of the one who has produced the text. Therefore, all the above-mentioned techniques have been used to disclose the hidden meaning intended by both authors within the two different poems whose contents corroborate the universal issues that are made to be human.